2011
DOI: 10.1007/s12598-011-0337-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cr-Fe coating on wettability of aluminum on ZTA ceramics

Abstract: The influence of Cr-Fe alloy coating on the spreading kinetics and contact angles of aluminum on ZTA ceramics were investigated using a sessile drop method. For this purpose, SEM and EDS were used to investigate the spreading kinetics transition of the reactive wetting system. The results show the contact angle of Al/ZTA is 88° at 1373 K, which is almost equal to that of Al/Al 2 O 3 and Al/ZrO 2 . Sputtering coated Cr-Fe film on ZTA substrate improves the wettability markedly. The contact angle decreases to 9.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…When chromium is present, the rate of oxidation slows down because chromium oxide is more stable than iron oxide and grows slower than iron oxide [8]. Several studies have shown that a high Cr in the composite may increase the wettability between ceramic and metal [9]. Therefore, it is very necessary to improve the Fe-Cr alloy to make these alloys last longer in the scientific field of metallurgy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When chromium is present, the rate of oxidation slows down because chromium oxide is more stable than iron oxide and grows slower than iron oxide [8]. Several studies have shown that a high Cr in the composite may increase the wettability between ceramic and metal [9]. Therefore, it is very necessary to improve the Fe-Cr alloy to make these alloys last longer in the scientific field of metallurgy.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is very necessary to improve the Fe-Cr alloy to make these alloys last longer in the scientific field of metallurgy. Recently there have been several techniques of strengthening metal matrices, such as alloying, precipitation strengthening, composites reinforcing, solid solution strengthening, and High energy milling may encourage the wettability of immiscible systems during the sintering, facilitate the interaction of component materials which also improve the strength [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [23] demonstrated that Cr-Ni alloy films could exhibit excellent hightemperature wear resistance. Wang et al [24] demonstrated that Cr-Fe interlayers could improve the wetting behaviours between Al and Zr 2 O 3 /Al 2 O 3 composites. The abovementioned results indicate that alloying of Cr films is a noteworthy attempt to explore the enhanced mechanical and functional properties of the films.…”
Section: Introductionmentioning
confidence: 99%